Pengaruh Jiwa Kewirausahaan dan Kemandirian Pribadi Terhadap Keberhasilan Usaha Kuliner Martabak di Jalan P. Antarsari Bandar Lampung - Kresna Bayu Adji; Tina Miniawati Barusman (Jurnal EMT KITA, 2023)
Amid the difficult circumstances of the pandemic, many of Martabak's merchants have expressed concern about declining sales. To address this situation, this study aims to explore the interplay between entrepreneurial spirit, personal independence, and business success of Martabak dealers on Antarsari Road. This study is based on robust numerical and quantitative data and utilizes advanced computational and statistical methods supported by SPSS 25 software for comprehensive data analysis. The findings highlight that both entrepreneurship and individual independence play an important role in the success of Antarsari Street Martabak merchants. As businesses grapple with the unprecedented challenges of the pandemic, these key factors are proving to be key drivers affecting overall business outcomes in this situation. By uncovering these key connections, this analysis aims to provide Martabak vendors with valuable insights to help them manage uncertainty in the pandemic era and adjust their strategies for lasting success.